1999
DOI: 10.1210/en.140.6.2908
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Induces Rat Ovarian Surface Epithelial Cell Mitosis or Apoptosis Depending on the Presence or Absence of an Extracellular Matrix

Abstract: The present studies showed that sequential treatment with equine CG (eCG) and hCG not only induced an increase in ovarian weight, but also caused an estimated 4.6-fold increase in the number of ovarian surface epithelial cells. In addition, eCG-hCG treatment increased ovarian hepatocyte growth factor (HGF) messenger RNA levels. These studies also demonstrated that rat primary ovarian surface epithelial cells as well as a cell line derived from rat ovarian surface epithelium (i.e. ROSE-179 cells) do not express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In this context, it can be expected that isolated OSE cells are unresponsive to reproductive hormones, just as the in vivo OSE in areas covering regressing corpora lutea or ovarian stroma. Several growth factors such as hepatocyte growth factor (HGF) (Hess et al 1999), and stem cell factor (SCF) (Parrot et al 2000), have been reported to regulate OSE cell proliferation in vitro. The expression of receptors for these growth factors in the OSE (Hess et al 1999, Parrot et al 2000, suggests that autocrine and paracrine routes are likely to be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it can be expected that isolated OSE cells are unresponsive to reproductive hormones, just as the in vivo OSE in areas covering regressing corpora lutea or ovarian stroma. Several growth factors such as hepatocyte growth factor (HGF) (Hess et al 1999), and stem cell factor (SCF) (Parrot et al 2000), have been reported to regulate OSE cell proliferation in vitro. The expression of receptors for these growth factors in the OSE (Hess et al 1999, Parrot et al 2000, suggests that autocrine and paracrine routes are likely to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…As the ovary is under the control of gonadotropins and steroids, these hormones are strong candidates to regulate the OSE. The potential for gonadotropins and steroids to regulate OSE cell proliferation is suggested by the demonstration of receptors for these hormones in the OSE of several species (HildPetito et al 1988, Zheng et al 1996, Pelletier et al 2000, Kuroda et al 2001, Okada et al 2002, although interspecies variations have been reported (Hess et al 1999, Pelletier et al 2000. In general, in vivo studies have reported that gonadotropins (Davies et al 1999, Hess et al 1999, Stewart et al 2004) and estrogens (Adams andAuersperg 1983, Bai et al 2000) stimulate OSE cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, HGF had been shown to induce apoptosis in a sarcoma cell line and in liver carcinoma models (21)(22)(23)(24). Furthermore, HGF induces death of ovarian surface epithelial cells when extracellular matrix or intercellular contacts are lacking (29,30). However, in all of these cases, HGF had a cytotoxic effect per se.…”
Section: Discussionmentioning
confidence: 99%
“…Because OSE cells are the cell type responsible for ovarian tumors, an understanding of the proliferative pathways used by these cells is of obvious importance. Although OSE cells show a proliferative response to a variety of stimuli, including follicle-stimulating hormone (2), hepatocyte growth factor (13), and elevated calcium (14,18), the relative importance of distinct signal transduction pathways in mediating the proliferation of OSE cells is not known.…”
mentioning
confidence: 99%